2022
DOI: 10.1038/s41598-022-17247-3
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D:4D) and maternal testosterone-to-estradiol ratio measured in early pregnancy

Abstract: The ratio of index to ring finger (2D:4D) has been hypothesised to indicate prenatal androgen exposure, yet evidence for its validity is lacking. We report the first pre-registered study to investigate mothers’ early pregnancy sex hormone concentrations in relation to their children’s digit ratios measured at 18–22-month follow-up. Although the testosterone (T) to estradiol (E) ratio correlated negatively with right hand digit ratio (R2D:4D) and directional asymmetry (right-minus-left) in digit ratio (D[R−L]),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 98 publications
0
5
0
3
Order By: Relevance
“…Furthermore, the studies on the digit ratios and testosterone could be enriched with consideration of other hormones, which might work in conjunction with testosterone, such as estradiol (Lutchmaya et al, 2004). Some evidence points to the association between the 2D:4D and testosterone to estradiol ratio (see, e.g., Richards et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the studies on the digit ratios and testosterone could be enriched with consideration of other hormones, which might work in conjunction with testosterone, such as estradiol (Lutchmaya et al, 2004). Some evidence points to the association between the 2D:4D and testosterone to estradiol ratio (see, e.g., Richards et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As Hollier, Keelan, Hickey, Maybery, and Whitehouse [70] discussed, to date there is no "gold standard" to examine hormone levels to which the fetus is exposed during pregnancy. Other studies have revealed inconsistent and mostly non-significant associations between children's 2D:4D and alternative measures like maternal plasma or cord blood samples to assess T levels in pregnant women [71][72][73][74].…”
Section: Plos Onementioning
confidence: 99%
“…Bireyin, anne karnında maruz kaldığı testosteron miktarının göstergesi olan 2D/4D parmak uzunluğu, gebelikte ve erişkin dönemde değişmemektedir. 1,2 2D/4D parmak oranının düşük olması doğum öncesi yüksek testosteron, düşük östrojen konsantrasyonu ile bağlantılıdır. 1 Bu nedenle 2D/4D parmak oranı androjen ve östrojenlere doğum öncesi maruz kalmanın bir belirteci olarak kullanılabilir.…”
unclassified
“…1,2 2D/4D parmak oranının düşük olması doğum öncesi yüksek testosteron, düşük östrojen konsantrasyonu ile bağlantılıdır. 1 Bu nedenle 2D/4D parmak oranı androjen ve östrojenlere doğum öncesi maruz kalmanın bir belirteci olarak kullanılabilir. 2D/4D ortalamalarında erkeklerin kadınlardan düşük olduğu bilinmektedir.…”
unclassified
See 1 more Smart Citation